2022
DOI: 10.31234/osf.io/pn4zd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-Commitment in Mental Imagery

Abstract: We examine non-commitment in the imagination. Across 5 studies (N > 1, 800), we find that most people are non-committal about basic aspects of their mental images, including features that would be readily apparent in real images. While previous work on the imagination has discussed the possibility of non-commitment, this paper is the first, to our knowledge, to examine this systematically and empirically. We find that people do not commit to basic properties of specified mental scenes (Studies 1 and 2),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…For example, McCoy and Ullman (2019) found that magical spells involving a physical transformation of an objects shape is judged as more effortful than a surface change of color. The physical and spatial properties of imagined entities (such as their size or relative location) also seem to be more likely to be committed to a mental scene than surface properties (such as color or texture, Bigelow et al, 2023). Despite the differences in the modes of imagination being investigated in prior literature and the current studies here, the findings across these works suggest a converging idea that the spatial and physical structure of objects guide much of people's imagination.…”
Section: Discussionmentioning
confidence: 48%
“…For example, McCoy and Ullman (2019) found that magical spells involving a physical transformation of an objects shape is judged as more effortful than a surface change of color. The physical and spatial properties of imagined entities (such as their size or relative location) also seem to be more likely to be committed to a mental scene than surface properties (such as color or texture, Bigelow et al, 2023). Despite the differences in the modes of imagination being investigated in prior literature and the current studies here, the findings across these works suggest a converging idea that the spatial and physical structure of objects guide much of people's imagination.…”
Section: Discussionmentioning
confidence: 48%
“…Their strength may stem from a very salient feature or from being able to picture a target in a very stable way. This may explain why subjects who report scant details about their mental images can still judge them to be vivid (Bigelow, McCoy, and Ullman 2023). Even within a single dimension, different objects can contribute to different degrees of strength.…”
Section: Beyond Painsmentioning
confidence: 99%